2019
DOI: 10.1519/jsc.0000000000003142
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of COL5A1, GDF5, and PPARA Genes on a Movement Screen and Neuromuscular Performance in Adolescent Team Sport Athletes

Abstract: and Pawel, Ci szczyk (2019) The effect of COL5A1, GDF5 and PPARA genes ę on a movement screen and neuromuscular performance in adolescent team sport athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…No significant associations were found for either of the following polymorphisms in the present study when corrected for gender: PPARA rs4253778, IL6 rs1474347, and PPARG rs1801282. For muscle function and jumping capacity, this is well in line with previous findings in other sports, at least for the PPARA rs4253778 polymorphism (Stastny et al, 2019). However, Stastny et al (2019) found significant associations to other muscle parameters, such as reactive muscle index.…”
Section: Effect Of Selected Genessupporting
confidence: 91%
“…No significant associations were found for either of the following polymorphisms in the present study when corrected for gender: PPARA rs4253778, IL6 rs1474347, and PPARG rs1801282. For muscle function and jumping capacity, this is well in line with previous findings in other sports, at least for the PPARA rs4253778 polymorphism (Stastny et al, 2019). However, Stastny et al (2019) found significant associations to other muscle parameters, such as reactive muscle index.…”
Section: Effect Of Selected Genessupporting
confidence: 91%
“…Especially, PPARA I7 rs4253778 CC genotype was rare ( n = 6) and might cause statistical bias. On the other hand, this rs4253778 CC genotype has been rare in previous studies on the Caucasian population, where it was shown to influence physical condition level [58,59]. The second question is whether the analyzed PPARA polymorphisms are true causative factors or perhaps only in linkage disequilibrium with variants directly engaged in developing a specific trait.…”
Section: Discussionmentioning
confidence: 96%
“…One might argue that trained compared to non-trained youth possess a higher amount of long-lasting, continuous and intense training experience [27]. Another reason might be the genetic profile of trained individuals [28,29]. For example, Murtagh et al [28] investigated the relationship of multiple single nucleotide polymorphisms with physical performance measures in elite male youth soccer players and control participants.…”
Section: Discussionmentioning
confidence: 99%